Area postrema syndrome: Frequency, criteria, and severity in AQP4-IgG–positive NMOSD. (23rd October 2018) - Shosha, Eslam; Dubey, Divyanshu; Palace, Jacqueline; Nakashima, Ichiro; Jacob, Anu; Fujihara, Kazuo; Takahashi, Toshiyuki; Whittam, Daniel; Leite, Maria Isabel; Misu, Tatsuro; Yoshiki, Takai; Messina, Silvia; et al.
Abstract : Objective: To define the frequency, duration, and severity of intractable nausea, vomiting, or hiccups in aquaporin-4–immunoglobulin G (AQP4-IgG)-positive neuromyelitis optica spectrum disorder (NMOSD) and propose diagnostic criteria and a severity scale for area postrema syndrome (APS). Methods: An International NMOSD database was interrogated for frequency of APS. Patients with AQP4-IgG–positive NMOSD completed an APS symptom questionnaire. Nausea and vomiting severity was derived from the Pregnancy-Unique Quantification of Emesis and Nausea (PUQE) score. The diagnostic criteria, severity scale, and immunotherapy response was applied to a prospective validation cohort of patients from multiple centers. Results: Analysis of an international database for AQP4-IgG–seropositive NMOSD (n = 430) revealed a high prevalence of isolated APS attacks (onset 7.1%–10.3%; subsequent 9.4%–14.5%) across continents. For 100 patients with 157 episodes of APS, nausea (n = 127, 81%) lasted for a median of 14 days (range 2–365), vomiting (113, 72%) with a median of 5 episodes/d (2–40) lasted 1–20 minutes, and hiccups (102, 65%) lasted a median of 14 days (2–365). Symptoms consistently and completely resolved following immunotherapy. Data were used to propose APS diagnostic criteria and repurpose PUQE score (hiccups severity grade based on symptom duration). The clinical utility was demonstrated in a prospective validation cohort. Conclusion: Isolated APS attacks are frequently encountered both at onset and during the NMOSD course. The diagnostic criteria proposed here will assist clinicians in recognizing APS. Diagnosis of an APS attack earlier than 48 hours is possible if a dorsal medulla lesion is detected. Accurate diagnosis and evaluation of APS attack severity will assist in outcome measurement in NMOSD clinical trials.